Sistema contable para la optimización de la planificación tributaria de la Distribuidora Velsuar - Gregor García, Melisa Lucia (2021)
This research seeks to implement a computerized accounting system to optimize the tax planning of Distribuidora "Velsuar", which allows determining the fair payment of taxes and faithful compliance with tax obligations and control entities, which will allow it to have a valuable tool to obtain real and timely information, to achieve efficient and effective administration. In the development of the theoretical framework, the main topics of an online computerized accounting system are described, among which we can mention: general aspects, characteristics, internal controls as a control tool. Among the research techniques used, surveys were prepared, which made it possible to collect information on the computerized accounting system used by microenterprises, as well as the reports they generate. The objectives of the investigation are also detailed.